Relationship between parental educational models and behavioural problems in students - Abellán Roselló, Laura (IE Revista de Investigación Educativa de la REDIECH, 2021)
The objective of this research is to indicate the most used parental upbringing model and if it is related to the students’ behavior problems, observed in the educational context. The sample was composed of 206 fathers and/or mothers of students between the ages of 4 and 16 (M = 8.3 and SD = 6.14), where 54.72% of the children are men and 45.28% are women, studying in kinder school (17.92%), elementary school (54.72%) or middle school (29.24%). The data was collected through the Parental Care Questionnaire and the ChildBehavior Checklist. An empirical-analytical study was carried out, with a transversal character, performing basic descriptive studies and bivariate linear correlation of Pearson. The results showed that the most widely used parental education model is the democratic one. It is also observed that the authoritarian model is related to behavioral problems. The implications of these findings for research and psychoeducational practice are discussed.